Assessment of ECG during hybrid comprehensive telerehabilitation in heart failure patients – subanalysis of the TELEREHabilitation in heart failure patients – TELEREH-HF randomized clinical trial. (14th October 2021) - Piotrowicz, E; Orzechowski, P; Zareba, W; Glowczynska, R; Szalewska, D; Pluta, S; Irzmanski, R; Kalarus, Z; Banach, M; Opolski, G; Pencina, M; Kowalik, I; et al.
Abstract: Background: Exercise training in heart failure (HF) patients (pts) should be monitored to ensure patients safety. That is why we use ECG telemonitoring during hybrid comprehensive telerehabilitation (HCTR). Purpose: Assessment of frequency of cardiac arrhythmias during telerehabilitation in HF patients. Methods: The present analysis formed part of TELEREH-HF multicenter, randomized (1:1), controlled trial that enrolled 850 HF pts with New York Heart Association class I, II, or III and left ventricular ejection fraction (LVEF) of 40% or less. Patients were randomized 1:1 to 9 week HCTR plus usual care or usual care only. This subanalysis focuses on 386 pts (aged 62±11 years, LVEF 31±7%) randomized to HCTR based on Nordic walking training 5 times/week. HCTR was tele-monitored with an EHO mini device adjusted to record 16-second fragments of ECG (from three precordial leads) and to transmit the data via mobile phone network to the monitoring center. The timing of automatic ECG recording were pre-set and coordinated with exercise training. Results: In all, 16622 HCTR sessions were registered and 66488 ECGs transmitted fragments were evaluated (four 16-second recording per patient per one session were recorded). A sinus rhythm was present in 320 (83%) pts, permanent atrial fibrillation in 66 (17%) pts. Assessment of ECG during HCTR procedure is presented in Table 1. Conclusions: Telerehabilitation in heart failure patients is safe without evidence for symptomatic cardiac arrhythmias requiring discontinuation of training. Non-sustained ventricular tachycardia and paroxysmal atrial fibrillation episodes were rare but have required adjustment of the telerehabilitation regimen. The most common arrhythmias were ventricular and supraventricular premature beats. These arrhythmias did not result in any changes in rehabilitation and therapy regimens. FUNDunding Acknowledgement: Type of funding sources: Other. Main funding source(s): The National Centre for Research and Development, Warsaw, Poland.